Annual Report 2012 - Forests, Trees and Agroforestry - Center for International Forestry Research (CGIAR Research Program on Forests, Trees and Agroforestry, 2013)
In this section, we provide a synthesis of the CGIAR Research Program on Forests, Trees and Agroforestry (CRP-FTA known internally and previously as CRP6), progress and the implementation challenges we have faced, our two greatest success stories for 2012, and an overview of our financial status. Abbreviations and references are listed at the end.